Forecasting the inevitable: A review on the impacts of climate change on renewable energy resources. (August 2022) - Russo, M.A.; Carvalho, D.; Martins, N.; Monteiro, A.
Highlights: Highest variation due to climate change impact is for long-term wind power. Disparities between forecasts of production and demand lead to uncertain estimates. Technological limitations need to be considered in future systems. Economic and societal aspects are key barriers for implementation of renewables. Uncertainties in modelling results is the most important issue across all studies. Abstract: Understanding the relationship and quantifying the impacts of climate change on energy production is key to meeting our objectives and achieving a sustainable future. Here we review the current state of the art on the methodologies to forecast future climate, potential changes in renewable energy production and main findings regarding the role of renewables in the decarbonisation of the energy supply. Most studies used a climate model and power production equations to estimate future renewable output. The largest variation in power production estimated was for the long-term climate change scenarios, with non-significant variations reported for the short-term. The highest variability was found for wind power followed by hydro, both in the long-term, and overall low variability for solar in any period. Additionally, future decarbonisation efforts point to investments in wind power as one of the main pillars of reducing fossil fuel dependency. Current knowledge gaps about the uncertainty of modelling results and the combined effects of climate change on renewable energy resources. Future studies should focus on increasing the resolution of climate models and improving input data, as well as assess the entire electricity production system and not concentrate on a single energy source, which will aid in defining decarbonisation strategies.